Effect of surface preparation on the strength of vibration welded butt joint made from PBT composite. (March 2020) - Showaib, Ezzat A.; Elsheikh, Ammar H.
Abstract: Vibration welding technique has been widely used to weld molded surfaces parts produced by injection or compression molding techniques. However, the majority of early studies used machined surfaces to eliminate the complication associated with molded surfaces. Different process parameters such as the welding pressure, frequency, and amplitude have been investigated to determine their optimal values that maximize the welding strength. However, some other parameters such as joint design and the welding interface preparation were leftover for real application test or for technology transfer studies. Most of molded parts from semi-crystalline materials and their composites usually have skin layer that was exposed to thermal history differs from that of the core. Moreover, the amount and the orientation of fibers in the skin layer differ from that of core and shell regions. Therefore, this work investigates and explores the effect of the molded surfaces with skin on tensile strength of vibration welded butt joints made from polybutylene terephthalate reinforced with 30% glass fiber (PBT GF30). The effect of fibers orientation on the welded joint strength has been also investigated. Highlights: The effect of surface preparation on the strength of vibration welded butt joint made from PBT composite has been investigated. Penetration for machined and molded surfaces during welding process is demonstrated. The effects of fibers orientation and welding pressure on the joint strength have been investigated. A tensile strength of welded samples close to that of the polymer matrix material could be achieved.